Improvement of the management of material and technical resources of water cleaning projects from explosive objects - Blintsov, Volodymyr; Hrytsaienko, Maksym (Technology audit and production reserves, 2016)
The object of research in the article is the management of material and technical resources of water cleaning projects from explosive objects in Ukraine. At this time, these projects are performed by State Emergency Service of Ukraine (SES) using diving technologies that endanger human life and health and has low productivity. Implementation of robotic technology for water cleaning from explosive objects in Ukraine is proposed using integrated involvement of marine robotics tools in SES expeditionary units consisting towed, self-propelled autonomous and remote-controlled underwater vehicles-robots, unmanned surface vessels and aircrafts. Project management process model of robotics of water cleaning from explosive objects is obtained as the component of management submodel of basic robotic underwater tasks and management submodel of the basic tasks on the effective use of special means of marine robotics. The obtained process model forms the theoretical basis for improving the management of material and technical of water cleaning projects through the use of safe and highly efficient robotic technologies for water cleaning. As a result of equipment of SES expeditionary units by specially developed or procured means of marine robotics will increase productivity and quality of marine operations as the tasks of national importance, and significantly decrease risks to life and health of people involved in such operations.